Simultaneous Oral and Umbilical Locations as a First Sign of Pemphigus Vulgaris - Eya Moussaoui; Yassine Oueslati; Lamia Oualha; Mohamed Denguezli; Badreddine Sriha; Nabiha Douki (Hindawi Limited, 2021)
The place of pemphigus vulgaris (PV) among autoimmune bullous diseases (AIBD) is well established. It is an acquired chronic, autoimmune, vesiculobullous disease in which IgG antibodies target desmosomal proteins to produce intraepithelial mucocutaneous blistering. The diagnosis is often challenging for the clinicians. It requires a combination of three major features: clinical, histopathological, and immunological. Clinically, oral lesions are the first manifestations of the disease in 50-90% of the patients with widespread blisters affecting the oral mucosa. On the skin, lesions are characterized by flaccid blisters that rapidly progress into erosions and crust formation. Umbilical lesions as a clinical manifestation of PV are peculiar and have rarely been reported, and they are not yet completely elucidated. Umbilical region involvement in patients with pemphigus was assessed in a limited study totalling just 10 patients. This localisation may be a valuable hint easing the diagnosis at the clinical level for patients with oral mucosal blisters. Dentists must be familiar with the clinical manifestations of PV to make an early diagnosis and start an early treatment which determines the prognosis of the disease. To the best of the authors' knowledge, the coexistence of these lesions with the oral lesions as a first sign of PV in the absence of skin involvement was reported in only one case of pemphigus vegetans (PVe). In this paper, we describe an observation of a female patient that was diagnosed with PV that begun with simultaneous oral and umbilical locations which coexisted for a period of 4 months before the appearance of other cutaneous lesions. We highlight the role of dentists, by being familiar with the clinical manifestations of PV, to make an early diagnosis to start an early treatment which determines the prognosis of the disease and to follow closely the evolution of lesions to change treatment if required. We also discuss the clinical, histological, and immunological features of the disease that enabled the differential diagnosis as well as the appropriate therapeutic management.